(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the formation of the ICT competence of higher education teachers. ICT competence of the modern teacher, we consider as a set of knowledge, skills, abilities and possessions of interest to modu late the training information, construction information and training field, the design of remote interaction, training, quality monitoring. Designing the use of ICT in the educational process, the teacher must analyze those possible direct and indirect effects on the student, which will determine its development.